Abreviasi dalam Komunitas Penggemar Musikal Touken Ranbu di Media Sosial X: Kajian Morfologi - Mufidah, Nabila Sri (KIRYOKU, 2024)
Social media Twitter or currently called X limits the number of words that can be used in one tweet, especially for free users. This words limitation means that users have to use abbreviations. Abbreviation is also used in various communities, for example the musical Touken Ranbu Fans Community called 刀ミュ実況・乾燥語り場 (Toumyu Jikkyou/Kansou gatari ba) or Touken Ranbu Musical Live Commentary Forum. This research aims to find the forms of abbreviations used in the community, then classify and describe them. This research also aims to classify the forms of abbreviation that appear based on the type of 名詞 (meishi, "noun") and the origin of the language that formed them. Methods used in this research are qualitative method and close reading technique. The results of the research show that there are 21 abbreviation data which are divided into 13 acronyms and 8 clippings. Then, if it is classified into meishi types, the data is divided into 11 固有名詞 (koyuu meishi), 2 動名詞 (domeishi), and 8 普通名詞 (futsuu meishi). Then, in terms of language origin, it is divided into 5 Japanese data, 9 English data, and 7 combination of Japanese and English data.